Head, heart, and hand : the Huguenot Seminary and College and the construction of middle class Afrikaner femininity, 1873-1910 - Duff, Sarah Emily (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (History))--University of Stellenbosch, 2006.